The contribution of cochlear implants to postural stability. (8th November 2017) - Shayman, Corey S.; Mancini, Martina; Weaver, Tyler S.; King, Laurie A.; Hullar, Timothy E.
Abstract : Objectives: To determine whether spatial auditory cues provided by cochlear implants can improve postural balance in adults with severe deafness. Methods: In the presence of spatial white noise, 13 adult cochlear implantees wore head and lumbar‐mounted inertial sensors while standing in the dark for 30 seconds in two auditory conditions: hearing assistive devices on and off. Results: Stability was improved with implants on (aided condition) compared to off (unaided condition) with respect to differences in mean head velocity (Cohen's d = 0.912, P = 0.006) as well as to root mean square (RMS) acceleration (Cohen's d = 0.456, P = 0.048). This was particularly evident in measures of anteroposterior accelerations (mean difference = 0.034 m/s 2 ; Cohen's d = 0.612; P = 0.011). Conclusion: The decrease in RMS head acceleration and velocity while wearing cochlear implants suggests that they could be recognized as balance implants in addition to auditory implants. The clinical importance of this finding in various patient populations remains to be determined. Level of Evidence: 4. Laryngoscope, 128:1676–1680, 2018